Cyberbullying dalam Perspektif Al-Qur’an: Analisis Interpretasi QS. Al-Hujurat: 11 dan QS. At-Taubah: 79 - Husaein Al Akbar Nasution; Indra. Harahap (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
Cyberbullying has emerged as a significant form of digital violence in line with the rapid development of information and communication technology. This phenomenon not only disrupts social relationships but also leads to serious psychological impacts such as anxiety, depression, and low self-esteem. This study aims to analyze cyberbullying from a Qur’anic perspective using a thematic exegesis approach integrated with social psychology. The research employs a qualitative method based on library research, focusing on the analysis of Qur’anic verses, particularly QS. Al-Hujurat: 11 and QS. At-Taubah: 79, which address ethical communication. The findings reveal that cyberbullying corresponds to behaviors explicitly prohibited in the Qur’an, including sukhriyah (mockery), lamz (insulting), tanābuz bi al-alqāb (name-calling), and istihzā’ (ridiculing). From a psychological perspective, these behaviors are associated with social aggression, low empathy, and the effects of anonymity in digital environments. The integration of Qur’anic exegesis and psychology demonstrates that Qur’anic values provide a strong ethical foundation for digital communication and serve as a preventive framework against the psychological harms of cyberbullying. This study contributes to the development of an interdisciplinary approach between Qur’anic studies and psychology, offering a contextual and applicable model of digital communication ethics based on Qur’anic values in the contemporary digital era.